Stem volume equation for constructing local volume table of Pinus merkusii Jungh et de Vriese in Tana Toraja community forest - Melewanto Patabang; Hardjanto Hardjanto (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2021)
Pinus merkusii Jungh et de Vriese is a plant with high market and economic values due to providing a variety of products, including wood. Good management is needed to preserve pine forest products. The first step toward effective forest management is developing a management plan based on estimated stock data. The volume table used has a significant impact on the accuracy of the stock potential estimate. This study aims to determine the best equation model for compiling a local volume table for P. merkusii Jungh et de Vriese in Tana Toraja Regency. The research was conducted at the community pine forest in Gandang Batu Sillanan and Mengkendek districts, Toraja Regency. The number of sample measured was 100 trees. An analytical method was used to calculate the amount of tree volume on allometric equations. The equation for the stem volume was made using the allometric equation. The research results showed that diameters' mean, standard deviation, and sampling error values were 28.34 cm, 7.39 cm, and 1.45, respectively, heights were 23.77 m, 7.37 m, and 1.44; volume was 1.44 m3, 0.96 m3, and 0.19. The regression equation modelling showed that the best equation model for estimating volume P. merkusii Jungh et de Vriese based on height and diameter was ????=????????2????.